Odpowiedzi

2009-11-12T18:03:19+01:00
1)m²-2m+mn-2n+m²+m-mn-n=2m²-m-n
2)(3x-2)(3x-2y+1)-4x(2x-3y+1)=9x²-6xy+3x-6x+4y-2-8x²+12xy-4x=x²+6xy-7x+4y-2
3)3mn-6m+3n-6+2mn-4n+2m-4=5mn-4m-n-10
4)x³-2x²+x²-2x-x³+2x²+x²-2x=2x²-4x
1 5 1
2009-11-12T18:06:07+01:00
A) (m+n)(m-2)+(m-n)(m+1)
m²+2m+mn-2n+m²+m-mn-n
2m²+3m-3n
b)(3x-2)(3x-2y+1)-4x(2x-3y+1)
9x²-6xy+3x-6x+4y-2-8x²+12xy-4x
x²+6xy-7x+4y-2
c)3(m+1)(n-2)+2(n+1)(m-2)
3(mn-2m+n-2)+2(mn-2n+m-2)
3mn-6m+3n-6+2mn-4n+2m-4
5mn-4m-n-10
d)x(x+1)(x-2)-x(x-1)(x-2)
x(x²-2x+x-2)-x(x²-2x-x+2)
x³-2x²+x²-2x-x³+2x²+x²2x
2x²-4x
2009-11-12T18:24:54+01:00
A) = m²+mn-2m-2n+m²+m-mn-n=2m²-m-n
b)= 9x²-6xy+3x-6x+4y-2-8x²+12xy-4x=x²-6xy-x-6x-2+4y-4x=x²-6xy- x-6x-2+4y-4x=x²-6xy-11x-2+4y

c) =3(mn-2m+n-2)+2(mn-2n+m-2)=3mn-6m+6n-6+2mn-4n+2m-4= 5mn-4m-2n-10
d) = x(x²+x+x-2)-x(x²-x+2-x)= x(x²+2x-2)-x(x²-2x+2)= x³+2x²-2x-x³+2x²-2= 4x²-2x-2

powinno być dobrze...